Strategi Kepala Sekolah Dalam Penguatan Budaya Mutu Pada Lembaga Pendidikan Islam - Yuris, Evicenna (Prodi PIAUD STAI Sumatera Medan, 2024)
This study aims to analyze the principal’s strategies in strengthening quality culture at the Islamic educational institution of SMK Bina Taruna 1 Medan. The background of this research stems from the need for Islamic-based vocational schools to not only produce graduates who are competent in vocational skills but also possess strong religious character as part of their institutional identity. This research employs a qualitative method with a phenomenological approach to explore the experiences, perceptions, and interpretations of the principal, teachers, administrative staff, and students regarding the implementation of quality culture. Data were collected through in-depth interviews, observations, and document analysis, then analyzed using data reduction techniques, data presentation, and the extraction of essential meanings. The findings show that the principal strengthens quality culture through visionary leadership, religious role-modelling, academic supervision, habituation of Islamic values, enhancement of teacher professionalism, and reinforcement of partnerships with industry and the community. The implementation of quality culture is evident through the integration of spiritual values with vocational standards, the application of industry-based learning, reinforcement of discipline, and continuous monitoring and evaluation. Supporting factors include strong leadership commitment, the school’s religious character, active participation of teachers and staff, and community support. Meanwhile, inhibiting factors involve inconsistency among some school members, limited facilities, and the influence of the surrounding social environment. This study offers novelty in the form of integrating quality management and Islamic values within the context of vocational schools, demonstrating that strengthening quality culture relies not only on formal policies but also on the internalization of religious values and exemplary leadership.